2021
DOI: 10.1038/s41467-021-25878-9
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Brønsted acid-controlled intermolecular asymmetric [2 + 2] photocycloadditions

Abstract: Control over the stereochemistry of excited-state photoreactions remains a significant challenge in organic synthesis. Recently, it has become recognized that the photophysical properties of simple organic substrates can be altered upon coordination to Lewis acid catalysts, and that these changes can be exploited in the design of highly enantioselective catalytic photoreactions. Chromophore activation strategies, wherein simple organic substrates are activated towards photoexcitation upon binding to a Lewis ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 51 publications
0
40
0
Order By: Relevance
“…However, cyclobutanes have four stereocenters, and their control suffers from relatively poor regio- and stereoselectivity 3 9 . Various supramolecular templates 10 12 , host-guest assemblies 13 , 14 , quantum dots 15 , chiral molecular catalysts 16 18 , and Lewis acid cocatalysts 19 , 20 have been developed to control the enantioselectivity and diastereoselectivity of [2 + 2] photocycloaddition transformations. Although it is possible to capture cyclic intermediates at low temperature 21 , the control of their stereochemistry during the reaction has not yet been documented.…”
Section: Introductionmentioning
confidence: 99%
“…However, cyclobutanes have four stereocenters, and their control suffers from relatively poor regio- and stereoselectivity 3 9 . Various supramolecular templates 10 12 , host-guest assemblies 13 , 14 , quantum dots 15 , chiral molecular catalysts 16 18 , and Lewis acid cocatalysts 19 , 20 have been developed to control the enantioselectivity and diastereoselectivity of [2 + 2] photocycloaddition transformations. Although it is possible to capture cyclic intermediates at low temperature 21 , the control of their stereochemistry during the reaction has not yet been documented.…”
Section: Introductionmentioning
confidence: 99%
“…8). 60,61 In both cases, enhanced yields and rate acceleration compared to the free cofactor were observed under optimized aqueous conditions. These improvements could result from increased local concentration of both substrate and photocatalyst within the ArM active site relative to solution.…”
Section: +mentioning
confidence: 89%
“…One of these involves 5-exo-trig reductive cyclization of dienones to generate 5-membered rings via electron transfer (Scheme 2a); 59 the second involves [2 + 2] cycloaddition between C-cinnamoyl imidazoles and different alkenes to give cyclobutanes via energy transfer (Scheme 2b). 60,61 Both reactions worked well in 10% aqueous ACN. Brønsted acid co-catalysts were not required in this medium, though a slightly acidic pH was optimal (ESI Fig.…”
Section: Pop Arms For Photocatalysismentioning
confidence: 95%
“…In 2019, Bach et al reported an intramolecular [2+2] photocycloaddition of 3-alkenyl-2cycloalkenones (27) to form photocyclization products (28) by utilizing a chiral oxazaborolidine Lewis acid catalyst (29) upon the irradiation of visible light (λ = 366 nm). The photocyclization products were produced well in yields and enantioselectivity (54-86% yield, 76-96% ee) (Scheme 7) [17].…”
Section: Enantioselective Formation Of 4-membered Ring By Visible Light Catalysismentioning
confidence: 99%
“…Scheme 13. Enantioselective intramolecular cyclization of 3-alkylquinolones.In 2021, Yoon et al used a chiral Brønsted acid (75) to obtain cyclobutane products (76) by asymmetric [2+2] photocycloaddition from α,β-unsaturated carbonyl compounds (77) and alkenes (78) in good yields and enantioselectivity (up to 85% yield, up to 99% ee) (Scheme 18)[28]. The reaction shows wide applicability, and some medicinally relevant motifs were also synthesized.…”
mentioning
confidence: 99%